1978
DOI: 10.1139/f78-205
|View full text |Cite
|
Sign up to set email alerts
|

Model for Examining Early Ocean Limitation of Pacific Salmon Production

Abstract: A computer simulation model was used to examine growth and survival of all major British Columbia salmon stocks during their first 6 mo of ocean life. Factors included in the calculations were the space–time distribution of zooplankton production, timing of salmon ocean arrival and migration especially as regards overlaps between stocks, feeding and growth in relation to food availability, and mortality rates in relation to body size. It is concluded that ocean limitation of production is unlikely unless only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
2

Year Published

1982
1982
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 0 publications
0
21
2
Order By: Relevance
“…An alternative hypothesis has been advanced that suggests there is a surplus of food resources for salmon in the ocean (Shuntov and Temnykh 2004). A similar food surplus hypothesis was advanced by Walters et al (1978) in British Columbia in the 1970s that spurred the rapid development of the Salmon Enhancement Program (or SEP) in Canada. Lack of success in meeting the fishery enhancement goals of that program and a better understanding of fish foraging behavior has led Walters to refute his original hypothesis (Walters and Juanes 1993).…”
Section: Ecological Interactions In Sakhalin Regionmentioning
confidence: 85%
“…An alternative hypothesis has been advanced that suggests there is a surplus of food resources for salmon in the ocean (Shuntov and Temnykh 2004). A similar food surplus hypothesis was advanced by Walters et al (1978) in British Columbia in the 1970s that spurred the rapid development of the Salmon Enhancement Program (or SEP) in Canada. Lack of success in meeting the fishery enhancement goals of that program and a better understanding of fish foraging behavior has led Walters to refute his original hypothesis (Walters and Juanes 1993).…”
Section: Ecological Interactions In Sakhalin Regionmentioning
confidence: 85%
“…(1999) reported that the growth of early migrating pink salmon was limited by the availability of pelagic prey. It is interesting to consider the match‐mismatch of sockeye migration timing and euphausiid prey availability in the context of investigations that suggested that juvenile salmonids would not be food‐limited in the sea (Walters et al. , 1978; Peterson et al.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of "biological windows" has been developed by numerous investigators (Walters et al 1978;Bilton et a]. 1982;Boeuf and Harache 1982;Holtby et al 1989) primarily to explain the timing of smolt migration relative to coastal predators, marine productivity, and oceanographic conditions that are likely determinants of early marine survival.…”
Section: Windows Of Biological Timeliness and Their Management Implicmentioning
confidence: 99%